A235 THE INFLUENCE OF IL10 ON COLITIS DEVELOPMENT IN NOD2 DEFICIENT MICE. (26th February 2020) - Gryfe, M D; Croitoru, K; Goethel, A; Luchak, A
Abstract: Background: Inflammatory bowel disease (IBD) risk genes include interleukin-10 ( IL10 ) and nucleotide-binding oligomerization domain-containing protein 2 ( NOD2 ). Although their specific roles in intestinal inflammation are unclear, these proteins are involved in modulating host-microbe interactions and intestinal homeostasis. Aims: Since IL10 is an anti-inflammatory cytokine that maintains intestinal homeostasis, we hypothesized that mice deficient for both IL10 and NOD2 would be more susceptible to colitis than mice with only the NOD2 deletion. Methods: In-house generated NOD2 -/- x IL10 -/- (double knockout) and NOD2 -/- x IL10 +/+ littermate mice of varying ages (3–20 weeks of age) were weighed and stools samples were collected at weekly intervals. Lipocalin-2 (LCN-2) levels were quantified in stool by ELISA. A subset of mice from each genotype received 3.5% dextran sulfate sodium (DSS) supplemented water for 5 days starting at eight weeks of age. Mice were sacrificed after two days of regular water, on day 8. Results: Untreated NOD2 -/- x IL10 +/+ mice showed higher fecal LCN-2 compared to NOD2 -/- x IL10 -/- mice at all ages, although this trend was not significant. Within DSS-treated mice, LCN-2 levels in stool collected at sacrifice (on day 8) were significantly higher in NOD2 -/- x IL10 +/+ mice, compared to NOD2 -/- x IL10 -/- mice. Moreover, only 50% (2 of 4) of the NOD2 -/- x IL10 +/+ DSS-treated mice survived to day 8, whereas all four NOD2 -/- x IL10 -/- DSS-treated mice survived. Conclusions: Fecal LCN-2 indicates the extent of neutrophil infiltration, which is reflective of the severity of intestinal inflammation. As such, LCN-2 levels suggest that NOD2 -/- x IL10 +/+ mice have higher baseline inflammation and are more susceptible to DSS-induced colitis than double knockout NOD2 -/- x IL10 -/ - mice. These results are contrary to our hypothesis that combining IL10 and NOD2 deficiency would increase colitis susceptibility as compared to NOD2 deficiency alone. This suggests that the absence of IL10 may actually reduce the severity of DSS-induced colitis in NOD2 deficient mice. The role of IL10 in modulating the gut microbiome using this model remains to be assessed. Funding Agencies: CAG